Home care for patients with COVID-19 by family caregivers during covid-19 pandemic - Martina Bedho; Sisilia Leny Cahyani (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: Covid-19 transmission is very easy, and simultaneously, resulting in a higher incidence of morbidity and mortality. The special incidence rate in Ende Tengah District, Onekore Health Center area, in February 2021 there were 11 close contacts, 42 people were the highest SWAB-PCR positive in Ende Regency, 2 people were isolated at the Ende Regional General Hospital, while 40 people were self-isolating. at home, 2 people died. Special attention from families is needed by treating patients in self-isolation according to health protocols, to prevent transmission of COVID-19. Purpose: To determine Covid-19 transmission to family caregivers during home care of members with COVID-19.Method: The design uses a mixed-method with a cross-sectional approach. The sample size is 40 self-isolated patients using total sampling. Data were collected using Chi-Square Bivariate Analysis and Multivariate Logistic Regression Test.Results: There is no effect of work on the prevention of Covid-19 transmission with the results of the bivariate statistical test p-value 0.232. There is an effect of self-isolation patient care at home in the variable not leaving the room, bivariate statistical test p-value = 0.001 ( p> 0.05). The results of the logistic regression statistical test p-value (2.211 - 47.842). However, there was no influence from the four variables, namely recognizing the signs and symptoms of severe Covid-19 ( p-value = 0.894), using the correct health protocol (p-value = 0.163), giving good nutrition (p-value = 0.087) and the needs of patients are served by healthy people (p-value = 0.308). The results of the logistic regression statistical test on the effect of recognizing severe symptoms of Covid-19, the p-value (0.198-6.385). The effect of using health protocols p-value (0.573-20.103) The effect of providing good nutrition p-value 1.476 ( 2.862). The effect of serving the needs of patients by healthy people is the p-value (0.407 – 15.751).Conclusion: The main treatment for self-isolated patients is that patients are not allowed to leave the room to prevent the transmission of Covid-19, by including counseling of family members by nurses at the community health center.